Preparation of modified porous steel slag/rubber composite materials and its properties - ZHANG Hao; ZHANG Xin-yu (工程科学学报, 2019)
High value-added utilization of solid wastes, such as the development of an inexpensive inorganic rubber filler, is one of the important approaches of sustainable development. Phosphoric acid, silane KH550, and steel slag were innovatively used to prepare modified porous steel slag, which partially replaced carbon black in this study. Modified porous steel slag was combined with carbon black, rubber, accelerator, sulfur, stearic acid, and zinc oxide to prepare a series of modified porous steel slag/rubber composite materials. This study investigated the mass ratios of phosphoric acid/steel slag, silane KH550/porous steel slag, accelerator/sulfur, and stearic acid/zinc oxide and the effect of the mass ratio of modified porous steel slag/carbon black on the mechanical properties of the prepared modified porous steel slag/rubber composite materials. At the same time, the influence mechanism was analyzed. The results indicate that the modified porous steel slag/rubber composites (the amounts of phosphoric acid, steel slag, silane KH550, carbon black, accelerator, sulfur, stearic acid, zinc oxide, and rubber are 1.2, 30, 0.3, 20, 0.8, 1.2, 0.8, 2.2, and 100 g, respectively) have good mechanical properties, with the tensile strength of 18.4 MPa, Shore A hardness of 68.8, and tearing strength of 44.6 kN·m-1. Phosphoric acid and silane KH550 can improve the pore and surface structures of steel slag. Appropriate ratios of accelerator/sulfur and stearic acid/zinc oxide can destroy the internal sulfur ring, which stabilizes the cross bond of rubber. Thus, a desirable package structure can be obtained by physically combining modified porous steel slag with rubber.